“Holy Rus’ bows before your feat, and future generations will bow before it with gratitude”: correspondence during the First World War between Valaam hegumen Mavrikiy (Baranov) and Grand Prince Nikolai Nikolaevich Romanov - Tatyana Shevchenko (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The publication covers correspondence during the First World War (1914-1917) between the abbot of the Valaam Transfiguration Monastery, Abbot Mauritius (Baranova, 1838-1918) with Grand Duke Nikolai Nikolaevich Romanov (1856-1929). A total of 35 letters and telegrams are presented. The correspondence is kept in the archives of the New Valaam Monastery in Finland. In 1914-1915 The Grand Duke was the Supreme Commander-in-Chief of the land and naval forces of the Russian Empire, then - the Viceroy of His Imperial Majesty in the Caucasus, the Commander-in-Chief of the Caucasian Army. The correspondence reflects the reactions of its authors to the military operations, successes and defeats of the Russian army, as well as the pastoral support of the Supreme Commander-in-Chief of the Abbot of Mauritius and the attitude of the Valaam abbot to the basic realities of the time, to the enemy countries of Russia and its allies, and reflects the Abbot’s thoughts about the future of Russia, about the Russian people, their place in history and in the world, about the significance of military feats, reflects the abbot’s hopes for a quick victory for Russia. The correspondence also contains several letters from the abbot to Grand Duchess Anastasia Nikolaevna, the wife of the Grand Duke, and her sister Militsa Nikolaevna, as well as their telegrams. Hegumen Mauritius was one of the most respected abbots of Valaam; he was a member of the Local Council in 1917. One of the most revered elders of the 20th century Hieroschemamonk Alexy Zosimovsky asked to take over his mantle before at the Council he drew lots with the name of the elected Patriarch, who became Metropolitan Tikhon (Bellavin) of Moscow and Kolomna.